The Effect of Price Perception, E-Service Quality, Brand Image on Spotify App Repurchase Interest Premium on National University Students - Irma Sifa Fauziah; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of perceived price, e-service quality, brand image on repeat purchase intention of students at the National University. The population in this study used the Non-Probability Sampling Technique with a population of 100 people, the students of the National University of Jakarta as respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 23 program. The results of the Multiple Linear Regression analysis show that the Price Perception variable (X1) has no positive and significant effect while E-Service Quality (X2) ¬), Brand Image (X3) has a positive and significant effect on Repurchase Intention (Y). The results of this study are expected to be able to increase Price Perception, E- Service Quality and Brand Image at the Spotify Company so that it can also increase existence and increase subscriptions for National University students.